Soil Organic Carbon in Typic Hapluderts on Different Slopes and Land Uses - Shofiana Kholifatul Fathonah Aulia; Mohammad Nurcholis (JOURNAL OF TROPICAL SOILS, 2026)
Organic carbon is a key component in the carbon cycle and plays a crucial role in determining soil quality. This research aimed to determine the soil organic carbon content on different slopes and land uses in Candirejo Village, Semin District, Gunungkidul Regency. Fieldwork was conducted using a survey method on Typic Hapluderts with varying slopes and land uses. Soil analyses included organic carbon, soil texture, soil bulk density, pH (H2O), and soil color. The results indicated that soil organic carbon levels varied across different slopes and land uses. Average soil organic carbon content on flat slopes was 1.64% (low), on sloping slopes it was 1.21% (low), while the land uses content from highest to lowest was in forests 2.19% (medium), in shrublands 1.55% (low), in settlements 1.31%, in dry lands 1.20% (low), and in paddy soils 0.86% (very low). Slope did not significantly influence soil organic carbon levels. However, land use significantly influences soil organic carbon levels, leading to substantial differences in soil organic carbon content. Soil color coordinate L* (lightness) is linearly negatively correlated with soil Organic-C, with a value of r = 0.641. Soil organic carbon showed a strong, significant relationship with the soil color coordinate L* (lightness). Higher soil organic carbon content was associated with lower L* values, indicating darker soil color.